2017
DOI: 10.1007/s11673-017-9773-1
|View full text |Cite
|
Sign up to set email alerts
|

The Role of a Hospital Ethics Consultation Service in Decision-Making for Unrepresented Patients

Abstract: Despite increased calls for hospital ethics committees to serve as default decision-makers about life-sustaining treatment (LST) for unrepresented patients who lack decision-making capacity or a surrogate decision-maker and whose wishes regarding medical care are not known, little is known about how committees currently function in these cases. This was a retrospective cohort study of all ethics committee consultations involving decision-making about LST for unrepresented patients at a large academic hospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 25 publications
0
22
0
1
Order By: Relevance
“…Studies in intensive care units revealed that 16 percent of patients admitted have no family or friend guardian (White, Curtis, Lo, & Luce, 2006), and these patients account for 5.5 percent of deaths annually (White et al, 2007). For those assessed in acute care settings, a large proportion of individuals without a family or friend guardian are admitted from nursing homes (Cohen, Benjamin, & Fried, 2019;Courtwright, Abrams, & Robinson, 2017;Griggins, Blackstone, McAliley, & Daly, 2019). Research estimates that older adults under public guardianship comprise 3 to 4 percent of the nursing home population, an estimate based on anecdotal information from focus groups of healthcare leaders (Karp & Wood, 2003).…”
Section: Research On Public Guardianshipmentioning
confidence: 99%
“…Studies in intensive care units revealed that 16 percent of patients admitted have no family or friend guardian (White, Curtis, Lo, & Luce, 2006), and these patients account for 5.5 percent of deaths annually (White et al, 2007). For those assessed in acute care settings, a large proportion of individuals without a family or friend guardian are admitted from nursing homes (Cohen, Benjamin, & Fried, 2019;Courtwright, Abrams, & Robinson, 2017;Griggins, Blackstone, McAliley, & Daly, 2019). Research estimates that older adults under public guardianship comprise 3 to 4 percent of the nursing home population, an estimate based on anecdotal information from focus groups of healthcare leaders (Karp & Wood, 2003).…”
Section: Research On Public Guardianshipmentioning
confidence: 99%
“…Generally, there is agreement that "a substituted judgement or a best interest standard" is best to help guide decision making for unrepresented patients, 9 although laws and policies vary in how best to uphold a best interest standard. 4,9 As the Hastings Center notes, "[t]here is as yet no consensus on the proper solution." 10 However, state laws and institutional policies attempt to solve the problem largely through 3 different approaches regarding the choice of decision maker: physician, ethics committee, and guardianship.…”
Section: Approaches To Making Decisionsmentioning
confidence: 99%
“…6,7 Deontological (duty-based obligation) analysis of error handling is further complicated, however, in situations in which the patient is both incapacitated and unrepresented, as is the case in roughly 8% of hospital ethics consultations nationwide. 2 This essay will propose a 3-part framework for error management pertaining to unrepresented patients. The first part concerns documentation and its role in informing future practice at both the physician and the systemic level.…”
Section: Commentarymentioning
confidence: 99%
“…Dr K feels that even if the patient were successfully resuscitated following another cardiac arrest, he would have very low quality of life, based on his knowledge of the literature. 1,2 Dr K thinks that it might now be best to change the 82year-old patient's code status to DNAR. However, Dr K is concerned that, given the erroneous first DNAR and the patient's unrepresented status, some members of the team might feel compelled to err on the side of providing more aggressive care.…”
mentioning
confidence: 99%